Torture based on discrimination in Chile.: The hunger strike of Mapuche political prisoners and the case of machi Celestino Cordova - Bustos, Jesus Antona (Torture Journal, 2020)
Of the approximately 40 Mapuche political prisoners currently serving sentences in Chilean jails, more than half have either gone on, or are currently on, hunger strike. The first prisoners to adopt such a measure did so on May 4. They are taking in liquids, but no solids, and so the state of health of many has now reached a critical level. Following substantial international pressure, the Chilean government has offered some minor prison benefits, however, there is no sign of measures to address neither the reasons for the strike, nor the torture perpetrated for reasons of discrimination that the Mapuche prisoners continue to suffer.